An international review of tobacco smoking in the medical profession: 1974-2004 - Smith Derek R; Leggat Peter A (BMC, 2007)
Abstract Background Tobacco smoking by physicians represents a contentious issue in public health, and regardless of what country it originates from, the need for accurate, historical data is paramount. As such, this article provides an international comparison of all modern literature describing the tobacco smoking habits of contemporary physicians. Methods A keyword search of appropriate MeSH terms was initially undertaken to identify relevant material, after which the reference lists of manuscripts were also examined to locate further publications. Results A total of 81 English-language studies published in the past 30 years met the inclusion criteria. Two distinct trends were evident. Firstly, most developed countries have shown a steady decline in physicians' smoking rates during recent years. On the other hand, physicians in some developed countries and newly-developing regions still appear to be smoking at high rates. The lowest smoking prevalence rates were consistently documented in the United States, Australia and the United Kingdom. Comparison with other health professionals suggests that fewer physicians smoke when compared to nurses, and sometimes less often than dentists. Conclusion Overall, this review suggests that while physicians' smoking habits appear to vary from region to region, they are not uniformly low when viewed from an international perspective. It is important that smoking in the medical profession declines in future years, so that physicians can remain at the forefront of anti-smoking programs and lead the way as public health exemplars in the 21st century.